2023
DOI: 10.1111/fare.12869
|View full text |Cite
|
Sign up to set email alerts
|

Screen use: Its association with caregiver mental health, parenting, and children's ADHD symptoms

Abstract: ObjectiveThe aim was to examine the relationship between caregiver's mental health (parental psychological distress, and parenting stress), dysfunctional parenting (lax or overreactive parenting), and the screen media use in understanding attention‐deficit/hyperactivity disorder (ADHD) symptoms of children within an integrated model framework.BackgroundFamilial factors and screen use have shown to be significantly related to ADHD in children. However, theoretical models of the role of family environment, scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
(92 reference statements)
0
0
0
Order By: Relevance
“…53 Waller et al found that parental psychological distress was positively associated with dysfunctional parenting (eg, laxness, over-reactivity), which in turn was associated with more screen time for children. 54 Furthermore, according to the IT-CPU, maintaining factors (eg, parents' NIUMP) were the mechanisms connecting proximal factors (eg, family distress) to problematic media use in children. 4 Thus, we proposed (H3) that NIUMP mediated the link between maternal COVID-19 distress and children's problematic media use.…”
Section: The Mediating Role Of Negative Instrumental Use Of Media In ...mentioning
confidence: 99%
“…53 Waller et al found that parental psychological distress was positively associated with dysfunctional parenting (eg, laxness, over-reactivity), which in turn was associated with more screen time for children. 54 Furthermore, according to the IT-CPU, maintaining factors (eg, parents' NIUMP) were the mechanisms connecting proximal factors (eg, family distress) to problematic media use in children. 4 Thus, we proposed (H3) that NIUMP mediated the link between maternal COVID-19 distress and children's problematic media use.…”
Section: The Mediating Role Of Negative Instrumental Use Of Media In ...mentioning
confidence: 99%